A feasibility study on Fruit Craze a complete fruit snack restaurant - Gigante, Mary Ann C.; Lebuna, Imee Claire C.; Patio, Ma. Katrina M.; Silva, Ramona E. (Quezon City College of Engineering, University of the Philippines Diliman, 2010)
Fruit Craze aspires to become a successful healthy restaurant bay offering fruits as the main ingredients of its recipes. In order to determine if that is possible, a four-month feasibility study was done. This paper present the feasibility study conducted for the Fruit Craze Restaurant. The feasibility study is divided into several phases: Market, Technical, Organizational, Financial and Social Profitability assessment. During the market study, the business concept was presented and later on modified based on the result of the study. In order to gather data from the consumers, surveys of random people about their fruit preferences and reaction to the Fruit Craze was done inside large malls in Quezon City such as SM North EDSA, Trinoma, and Farmer's Plaza. Based on the survey and statistical data gathered through research, an initial demand of 405,667 was computed. The industry analysis helped in identifying the competitors and marketing strategy needed. To achieve focus, the study was centered on the Quezon City area only. The technical study yields the information about how the Fruit Craze will operate. The target location which is the SM North EDSA in Quezon City was identified after evaluating the existing malls in Quezon City in terms of several factors such as foot-trafic and leasing cost. Suppliers for raw materials are also evaluated based on a certain criteria that focus on the quality of raw materials being delivered. The equipment needed and layout of the restaurant was also identified. Fruit Craze will operate under sole proprietorship as determined in the organizational study. The minimum manpower requirement and expenses was also determined based on the task allocation and compensation of the 8 employees of the restaurant. A total project cost of Php 1,859,330 was computed during the financial study. Two types of financing will be used: dept and equity financing. The Php1,000,000 will be loaned from Land Bank under the Department of Trade and Industry Sulong Program for SMEs while the remaining Php 859,330.00 will be provided by the owner. With this financing and the expected retained earnings of 914,168 during the first year with an increasing pattern value of the business is determined to be Php 6,030,922.62, a value that signals the profitability of the business. This means that Fruit Craze is capable of generating profit thus, a worthy investment. For the Fruit Craze to be valuable investment not only for the limited stakeholders but to the whole society as well, the social-profitability study was conducted. It has been determined that it can contribute economically through generation of jobs and patronization of local businesses. Throughout this feasibility study, the concept of the Fruit Craze has been able to satisfy the requirements and flexible enough to be modified into a better project. At the end of the study, a Fruit Crzae restaurant that is feasible enough to be built was established.
Keywords: Restaurants -- Design and construction; Natural food restaurants; Feasibility studies